Dynamic investigation of a seven-tier container stack with different lashing arrangements subject to rolling and pitching excitation. (3rd July 2022) - Li, Chuntong; Cai, Zhonghua; Wang, Deyu
ABSTRACT: The current safety assessments of lashing systems and container stacks in various classification societies are based on static conditions, while dynamic behaviours are neglected. In this paper, the dynamic mechanical behaviour of a seven-tier 20-ft ISO freight container single stack and lashing devices under the combined rolling and pitching excitation is studied respectively. Through experiments and numerical simulations, five typical lashing arrangements are compared. The results show that a reasonable configuration of lashing stiffness, twist lock gap and lashing arrangement can decrease the dynamic response of the system. The external lashing arrangement is more suitable for the heavy stowage situation. The twist lock structure is more prone to failure in the horizontal direction than in the vertical direction, and a reasonable horizontal gap can effectively prevent the shear force from exceeding the allowable value. Finally, the benefits and drawbacks of each lashing arrangement for shipping companies are discussed.